Serine/Threonine Kinase 40 (Stk40) Functions as a Novel Regulator of Skeletal Muscle Differentiation - He, Ke (J Biol Chem, 2017)
Skeletal muscle differentiation is a precisely coordinated process, and the molecular mechanism regulating the process remains incompletely understood. Here we report the identification of serine/threonine kinase 40 (Stk40) as a novel positive regulator of skeletal myoblast differentiation in culture and fetal skeletal muscle formation in vivo. We show that the expression level of Stk40 increases during skeletal muscle differentiation. Down-regulation and overexpression of Stk40 significantly decreases and increases myogenic differentiation of C2C12 myoblasts, respectively. In vivo, the number of myofibers and expression levels of myogenic markers are reduced in the fetal muscle of Stk40 knockout mice, indicating impaired fetal skeletal muscle formation. Mechanistically, Stk40 controls the protein level of histone deacetylase 5 (HDAC5) to maintain transcriptional activities of myocyte enhancer factor 2 (MEF2), a family of transcription factor important for skeletal myogenesis. Silencing of HDAC5 expression rescues the reduced myogenic gene expression caused by Stk40 deficiency. Together, our study reveals that Stk40 is required for fetal skeletal muscle development and provides molecular insights into the control of the HDAC5-MEF2 axis in skeletal myogenesis.